A PRDX1-p38α heterodimer amplifies MET-driven invasion of IDH-wildtype and IDH-mutant gliomas - Wirthschaft, Peter; Simon, Anika; Bucher, Delia; Hahn, Artur; Sahm, Felix; Breckwoldt, Michael O.; Kurz, Felix T.; Hielscher, Thomas; Dross, Nicolas; Ruiz de Almodóvar, Carmen; Deimling, Andreas von; Herold-Mende, Christel; et al. (International journal of cancer, 2018)
The Peroxiredoxin 1 (PRDX1) gene maps to chromosome arm 1p and is hemizygously deleted and epigenetically silenced in isocitrate dehydrogenase 1 or 2 (IDH)-mutant and 1p/19q-codeleted oligodendroglial tumors. In contrast, IDH-wildtype astrocytic gliomas including glioblastomas mostly lack epigenetic silencing and express PRDX1 protein. In our study, we investigated how PRDX1 contributes to the infiltrative growth of IDH-wildtype gliomas. Focusing on p38α-dependent pathways, we analyzed clinical data from 133 patients of the NOA-04 trial cohort to look for differences in the gene expression profiles of gliomas with wildtype or mutant IDH. Biochemical interaction studies as well as in vitro and ex vivo migration studies were used to establish a biological role of PRDX1 in maintaining pathway activity. Whole-brain high-resolution ultramicroscopy and survival analyses of pre-clinical mouse models for IDH-wildtype gliomas were then used for in vivo confirmation. Based on clinical data, we found that the absence of PRDX1 is associated with changes in the expression of MET/HGF signaling components. PRDX1 forms a heterodimer with p38α mitogen-activated protein kinase 14 (MAPK14), stabilizing phospho-p38α in glioma cells. This process amplifies hepatocyte growth factor (HGF)-mediated signaling and stimulates actin cytoskeleton dynamics that promote glioma cell migration. Whole-brain high-resolution ultramicroscopy confirms these findings, indicating that PRDX1 promotes glioma brain invasion in vivo. Finally, reduced expression of PRDX1 increased survival in mouse glioma models. Thus, our preclinical findings suggest that PRDX1 expression levels may serve as a molecular marker for patients who could benefit from targeted inhibition of MET/HGF signaling.